Bioinformatics Study: Molecular Docking of Cat Whiskers Flavonoid Compounds for the Development of Antidiabetic Candidates - Amin, Saeful; Rusdaita, Febia Citraeni; Prasetiawati, Riska (Journal of Information System, Technology and Engineering, 2024)
Diabetes mellitus is a chronic disease characterized by hyperglycemia. In silico studies have been done on flavonoid derivative compounds from the cat's whiskers plant (Orthosiphon stamineus Benth.) on protein tyrosine phosphatase 1B (2F70) and aldose reductase enzymes (4YVP and 4YVX) to see if they can be used as diabetes medicines. The molecular docking of the test compounds found three that were more active than the comparison ligands. One of these was the luteolin compound, which can stop the Protein Tyrosine Phosphatase 1B receptor from working with an ∆G value of -8.05 kcal/mol and a Ki value of 1.25 µM by forming amino acid residues. SER A: 216, ARG A: 221, ALA A: 217, VAL A: 490, TYR A: 46, and ASP A: 181 show that the sinensetin compound can stop the aldose reductase enzyme from working, working with a ∆G value of -7.72 kcal/mol and a Ki value of 2.19 µM to form amino acid residues. ALA B: 25, GLU B: 224, LEU B: 54, HIS B: 222, TRP B: 227, and the 6-hydroxy-5,7,4'-trimethoxyflavone compound can stop the aldose reductase enzyme from working (∆G value of -7.02 kcal/mol, Ki 7.14 µM), which creates amino acid residues. HIS B:117, TYR B:55, SER B:217, PHE B:306. Based on the analysis of these compounds, they exhibit good physicochemical and pharmacokinetic profiles. Additionally, the toxicity analysis confirms that none of these compounds are mutagenic, carcinogenic, or harmful to humans.